Reconsiderations for Effective Financial Policy after Korean Currency Crisis - Chong Ook Rhee (East Asian Economic Review, 2000)
From the empirical findings, we can conclude that the capital liberalization after the Korean currency crisis strengthened the financial linkage with international financial centers. It means that Korean policy makers have to consider foreign as well as domestic situations in designing effective financial policies. This paper suggests seven points to be included in the new dimensions of Korean financial policy. First, Korean government has to minimize policy mistakes, to enact monetary policy more carefully, and to develop financial institutions to provide variety of financing in the domestic economy. Second, Korean government has to promote international policy cooperation and to participate in establishing a new international regime that could reflect its own situations.